1981
DOI: 10.1017/s0043174500039928
|View full text |Cite
|
Sign up to set email alerts
|

Response of Small-Grain Cultivars to Chlorsulfuron

Abstract: The response of several spring wheat (Triticum aestivum L.), barley (Hordeum vulgare L.), and oat (Avena sativa L.) cultivars to preemergence and postemergence applications of chlorsulfuron (tested under code number DPX-4189) {2-chloro-N-[[(4-methoxy-6-methyl-1,3,5-triazin-2-yl)aminocarbonyl] benzenesulfonamide} was evaluated in the field and greenhouse in 1979. In greenhouse experiments, ‘Butte’ spring wheat was less susceptible than six other spring wheat cultivars to chlorsulfuron at 1.0 kg/ha applied preem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…The detachment of leaf 4 of Rongotea following chlorsulfuron application is similar to results in previous reports for wheat (Hageman & Behrens, 1981) and velvetleaf {Abutilon theophrasti Medic; Hageman & Behrens, 1984), Reductions in dry weight were always greater at the earlier harvests and all cultivars showed considerable recovery from the early damage. Similarly, Royuela et aL (1990), found that phytotoxic effects from chlorsulfuron were less evident at the heading stage than at tillering in winter wheat.…”
Section: Discussionsupporting
confidence: 89%
“…The detachment of leaf 4 of Rongotea following chlorsulfuron application is similar to results in previous reports for wheat (Hageman & Behrens, 1981) and velvetleaf {Abutilon theophrasti Medic; Hageman & Behrens, 1984), Reductions in dry weight were always greater at the earlier harvests and all cultivars showed considerable recovery from the early damage. Similarly, Royuela et aL (1990), found that phytotoxic effects from chlorsulfuron were less evident at the heading stage than at tillering in winter wheat.…”
Section: Discussionsupporting
confidence: 89%
“…Wicks et al [22] and Bailey et al [23] reported no wheat injury with thifensulfuron/tribenuronmethyl applied POST at 47 g·ha −1 in Virginia, USA. Hageman and Behrens [24] found as much as 11% injury with chlorsulfuron another sulfonylurea herbicide in wheat.…”
Section: Resultsmentioning
confidence: 99%
“…Mesotrione applied POST caused a decrease in the yield of spring wheat of up to 14% [20]. Hageman and Behrens [3] found as much as 30% yield reduction with chlorsulfuron in durum wheat under some environments at Minnesota, USA.…”
Section: Yieldmentioning
confidence: 96%
“…Wicks et al [14] and Bailey et al [15] reported no wheat injury with thifensulfuron-methyl plus tribenuron-methyl applied POST at 47 g·ha -1 in Virginia, USA. Hageman and Behrens [3] found as much as 11% injury with chlorsulfuron another sulfonylurea herbicide in durum wheat at Minnesota, USA.…”
Section: Injurymentioning
confidence: 99%
See 1 more Smart Citation